Persepsi Pelaku UMKM Terhadap Alternatif Model Pemungutan Pajak UMKM dengan Pemanfaatan Teknologi QRIS - Riani Budiarsih; Hartono Sony (Politeknik Keuangan Negara STAN, 2022)
Efforts to optimize tax revenue from the MSME sector require innovation from the Directorate General of Taxes to improve tax compliance of MSME actors. So far, MSME actors have calculated themselves from the turnover they generate and then every month they periodically pay their taxes and report them to the Tax Office. The presence of QRIS technology has now been widely adopted by MSME actors in payment transactions. Several local governments have also started using QRIS for local tax payments. This study used the method of filling out questionnaires and interviews. The results showed that the non-compliance of MSMEs in paying taxes was not because they objected to paying taxes of 0.5%, but rather the tax administration process which was considered troublesome and impractical for them. The proposed model, namely the integration of tax collection through QRIS technology, received a positive response from MSME actors because theoretically it offered the practicality, convenience, and effectiveness of tax collection.